EU VALUES IN REFORMING PUBLIC ADMINISTRATION - Bratashova Y. (Theory and Practice of Public Administration, 2019)
The article analyzes the reform of public administration systems based on the common values of the European Union in accordance with the Association Agreement between Ukraine, on the one hand, and the European Union, the Atomic Energy Community and their Member States, on the other hand, namely:– adherence to democratic principles: recognition the people as a source of power and a carrier of sovereignty; equality of citizens (true, only formal and legal), equal opportunity to participate in political life; the existence of fundamental human rights and freedoms, their recognition, guarantee and protection by the state; the principle of majority is precisely the majority, not the minority, expressing their will through the institutions of democracy; the right of the minority to the opposition (subject to majority decisions; political pluralism, ie the presence of various autonomous socio-political parties, movements, groups in a state of free competition; the rule of law - a kind of democratic state where the political regime relies on strict compliance with the rule of law rules that enshrine the natural, inalienable, universal rights and freedoms of man and peoples; a system of separation of powers in which the various branches of state power are sufficiently independent and counterbalance one another, hampering institutions ennyu dictatorship; transparency in the actions of state bodies and officials, the possibility of unrestricted control over them by society, the main election authorities by universal and direct suffrage by secret ballot, a developed system of local government;– the rule of law provides for lawfulness, including transparent, accountable and democratic enforcement; legal certainty; prohibition of arbitrariness; access to justice in independent and impartial courts, including judicial review of administrative acts; respect for human rights; non-discrimination and equality before the law. The rule of law in accordance with the Constitution of Ukraine is recognized and enforced in Ukraine;– Good governance: fair elections, representation and participation; feedback; efficiency and effectiveness; openness and transparency; Rule of Law; ethical behavior; competence and ability; innovation and openness to change; sustainable development and strategic orientation; sound financial management; human rights, cultural diversity and social cohesion.It has been proved that reforming the system of public administration and the transition in modern conditions of development to public administration changes the system of values ​​that are common to the democratic states of the world and create the conditions of the rule of law and government based on good governance.